2023
DOI: 10.1186/s13195-023-01174-0
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of plasma biomarkers across the Alzheimer’s continuum

Abstract: Background Failures in drug trials strengthen the necessity to further determine the neuropathological events during the development of Alzheimer’s disease (AD). We sought to investigate the dynamic changes and performance of plasma biomarkers across the entire Alzheimer’s continuum in the Chinese population. Methods Plasma amyloid-β (Αβ)42, Aβ40, Aβ42/Aβ40, phosphorylated tau (p-tau)181, neurofilament light (NfL), and glial fibrillary acidic prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…Elevated plasma GFAP levels were observed in cognitively intact individuals with Aβ positivity, particularly distinguishing Aβ+ from Aβ− individuals (Chatterjee et al, 2022). GFAP emerged as the earliest and most significantly altered biomarker from preclinical to symptomatic AD, predicting progression and cognitive decline (Guo et al, 2023; Shen et al, 2023). While GFAP levels can be influenced by other neuroinflammatory factors (Abdelhak et al, 2022), integrating multiple plasma biomarkers with structural efficiency can enhance the precision of staging patients along the AD continuum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated plasma GFAP levels were observed in cognitively intact individuals with Aβ positivity, particularly distinguishing Aβ+ from Aβ− individuals (Chatterjee et al, 2022). GFAP emerged as the earliest and most significantly altered biomarker from preclinical to symptomatic AD, predicting progression and cognitive decline (Guo et al, 2023; Shen et al, 2023). While GFAP levels can be influenced by other neuroinflammatory factors (Abdelhak et al, 2022), integrating multiple plasma biomarkers with structural efficiency can enhance the precision of staging patients along the AD continuum.…”
Section: Discussionmentioning
confidence: 99%
“…While blood levels of neurofilament light (NfL) and glial fibrillary acidic protein (GFAP) are abnormal in a range of neurodegenerative disorders, there is a growing body of research that explores the potential of these markers as biomarkers for AD (Benedet et al, 2021; Mattsson et al, 2019). A recent investigation revealed that plasma levels of GFAP experience a noteworthy elevation during the preclinical stage of AD (Guo et al, 2023). Moreover, plasma GFAP exhibits the most effective performance for monitoring longitudinal disease progression (Chatterjee et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, this profile has been utilized in many studies for different research purposes in AD, including exploration of the concordance and discordance between the A/T/N profile and clinical diagnosis, 2–4 investigation of the association between the A/T/N profile and cognitive change, 3,5–7 the risk of mortality, 8 and the risk factor, 9,10 detection of the changes of AD‐related markers over the A/T/N profiles, 6,11–14 and the use of the A/T/N biomarkers alone or in combination to determine optimal diagnostic markers 15,16 . With the development of high‐performing assays for plasma biomarkers, increasing studies have investigated plasma‐related A/T/N biomarkers against the pathological outcome based on PET or CSF biomarkers 17–20 . These studies have shown great promise for the potential of the A/T/N profile in predicting AD diagnosis and disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 With the development of high-performing assays for plasma biomarkers, increasing studies have investigated plasmarelated A/T/N biomarkers against the pathological outcome based on PET or CSF biomarkers. [17][18][19][20] These studies have shown great promise for the potential of the A/T/N profile in predicting AD diagnosis and disease progression. However, few studies investigated the association between the A/T/N profile and the gold-standard neuropathology of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Two robust fluid biomarkers for measuring astrocyte reactivity in vivo are glial fibrillary acidic protein (GFAP) and chitinase‐3‐like protein 1 (YKL‐40), 12 both of which have consistently been found to be elevated in the dementia phase of AD 13–15 . Recent work has suggested that changes in astrocytes arise very early in the course of AD, prior to frank neurodegeneration and cognitive impairment, demonstrating an upregulation of GFAP and YKL‐40 levels in Aβ‐positive cognitively unimpaired (CU) individuals 16–22 . In particular, plasma GFAP, rather than GFAP in cerebrospinal fluid (CSF), has demonstrated superior performance in detecting Aβ‐positive CU individuals 17,23,24 .…”
Section: Introductionmentioning
confidence: 99%